Conceptual Frameworks for Understanding Postnatal Mothers’ Satisfaction with the Birthing Experience: A Narrative Review - Zulu, Mutinke; Vwalika, Bellington; Maeland, Kaorolin; Kwaleyela, Concepta (British Journal of Healthcare and Medical Research, 2026)
Modern healthcare is increasingly emphasizing maternal satisfaction as the most important qualitative outcome of the childbirth experience. This narrative review aimed to categorize and evaluate the conceptual frameworks used to define and measure maternal satisfaction. A comprehensive search was conducted across electronic databases, including PubMed, EMBASE, and the Cochrane Library, supplemented by Google Scholar and Semantic Scholar. The AI tool Elicit was utilized to assist in screening scientific papers for thematic relevance. Search terms included satisfaction, conceptual frameworks, birthing experience, and postnatal mothers. This narrative review identifies a spectrum of frameworks varying in scope, focus, and theoretical origin. The Donabedian framework remains the foundational model for quality, while the WHO quality of care framework for maternal and neonatal health provides a holistic policy perspective by elevating respectful maternity care to a core dimension. The Hulton framework emphasizes institutional assessment. In contrast, the Hollins Martin and Dencker models are patient-driven, prioritizing internal, subjective experiences and patient-reported factors. The findings suggest a divide between the top-down quality assurance models (Donabedian, Hulton, WHO) and bottom-up, experience-based models (Hollins Martin, Dencker). No single framework provides a comprehensive multidimensional understanding of maternal satisfaction. This review suggests that researchers should consider integrating structural quality indicators with subjective patient-reported dimensions to fully capture the complexity of the birthing experience.